IMPEMENTASI PEMBERIAN KOMPENSASI TERHADAP KORBAN TINDAK PIDANA TERORISME BERDASARKAN UNDANG-UNDANG REPUBLIK INDONESIA NOMOR 31 TAHUN 2014 TENTANG PERLINDUNGAN SAKSI DAN KORBAN - yun Frida Isnaini; Abdul Haris Semendawai; Syarif Fadillah (Fakultas Hukum, Universitas Islam As-Syafi'iyah, 2020)
Yun Frida Isnaini, 1220160023, The Implementation of Compensation for Victims of CriminalActs Terrorism According to concerning Protection of Witnesses and Victims Law Number 31 of2014. Faculty of Law, Universitas Islam As-Syafi’iyah, 2020. This study elaborate on theprotection of victims of terrorism according to the Protection of Witnesses and Victims Law. Thisstudy aims to determine that there is a need for compensation for victims of criminal acts ofterrorism in Indonesia, as well as for criminal acts of terrorism to be compensated based on thelaws in Indonesia. The research was conducted by analyzing court decisions. In addition, theauthor also conducts literature studies by examining books, literature, and invitation regulationsrelated to the problems that the author discusses in this thesis. The results of the research showthat: (1) The mechanism for providing compensation by the Witness and Victim Protection Agencythrough court decisions, (2) Compensation is a form of state responsibility for victims of criminalacts of terrorism.